Forest-Induced Exponential Growth of PrecipitationAlong Climatological Wind StreamlinesOver the Amazon (2019)
ABSTRACT: The Amazon forests and climatological precipitation patterns in South America areinterrelated. A fundamental question is how these patterns depend on the presence of forests. Here weinvestigate this relationship by studying how precipitation varies with distance from the ocean along windstreamlines linking the Atlantic Ocean to northwestern and southern South America through the Amazonforests. Through a robust observation-based analysis, we found that precipitation exponentially increaseswith distance from the ocean along wind streamlines flowing over forests, while it exponentially decreasesdownwind of the forests. These patterns are consistent with multiple mechanisms through which forestsinfluence the transport of atmospheric moisture and precipitation production over the continent. Wepropose a conceptual explanation of this forest influence based on the atmospheric water balance. Ourresults imply that a major consequence of the degradation or loss of forests may be a disruption of thesemechanisms, with widespread impacts on continental precipitation.